Стратегія економічного розвитку Британської Вест-Індії у 1930–1960-х рр. - Брайлян, Є. (Український історичний збірник, 2017)
У статті охарактеризовано еволюцію візії економіки британських володінь
в Карибському басейні в новітній період. Відзначено джерелознавчий, історіографічний та міждисциплінарний аспекти даної проблематики. Проаналізовано у компаративістському ключі підходи національний лідерів, колоніальних чиновників, економістів, вчених з Кембріджу. Визначено магістральні напрямки економічного розвитку карибських колоній. Наприкінці 1920-х — на
початку 1930-х рр. британська метрополія, в тому числі Колоніал Офіс почали
розробляти стратегічне планування імперської економіки, що було уособлено
згодом Актами Колоніального Розвитку та Добробуту в 1929 р., 1940 р.,
1945 р., 1949 р., 1950 р., 1955 р., 1959 р., 1963 р. Період 1930–1960-х рр. позначений структурними змінами економіки Британської Вест-Індії в промисловості, аграрному секторі, туризмі, інфраструктурі. Нині, незважаючи на
тривалі дослідження в галузі британістики, колоніальних та постколоніальних
студій аналіз середньострокого економічного планування актуальною та перспективною тематикою для вітчизняних науковців. The article describes the evolution of the vision of the economy of British
possessions in the Caribbean in the contemporary period. Primary sources, historiographical
and interdisciplinary aspects of this paper are noted. Comparative
analysis of key approaches of national leaders, colonial officials, economists,
scientists from Cambridge is shown. Main directions of economic development of the
Caribbean colonies are defined. At the end of 1920s — early 1930s British metropolis,
including the Colonial Office began to develop strategic planning of imperial economy,
which was embodied later Acts of the Colonial Development and Welfare in
1929, 1940, 1945, 1949, 1950, 1955, 1959, 1963. In the late 1930s, the Colonial
Secretary Malcolm convinced the metropolitan government to invest £5 million per
year for the next twenty years to promote economic development and fund social
welfare in the colonies. The Development and Welfare Organisation of the West Indies
was established in 1940, assisted the allocation of British funds and loans to the
region. In 1948, the Labour government created the Overseas Food Corporation and
the Colonial Development Corporation, which aimed to use state funds to channel
capital into export-related colonial projects that had difficulty attracting private
investment. With the expiry on 31 March, 1970 of the Overseas Development and
Service Act, 1965, the Colonial Development & Welfare system came formally to an
end. Period of 1930–1960-s was marked by structural changes in the economy of the
British West Indies in industry, agriculture, tourism, infrastructure. In the 1930s the
international depression savagely hit the precarious economies of the West Indies.
Today, despite lengthy research in British studies, colonial and postcolonial studies
analysis of medium-term economic planning is urgent and promising theme for
Ukrainian scientists.